"The vile conclusion". Crises of resolution in Shakespeare's love plots. (2nd July 2016) - Wiebracht, Ben
Abstract : This article offers a new perspective on closure in Shakespeare's plays by adopting a theory of narrative dynamics, most commonly associated with Peter Brooks, that has until now been applied predominantly to the novel. According to this theory, plot and resolution are not distinct phases in the story, but dueling forces that contend throughout it, the one complicating and sustaining the narrative, the other simplifying and resolving it. This article shows that for Shakespeare, romantic love was deeply implicated with the former. In the literature of Shakespeare's day, romantic love was understood to be an inherently destabilizing force – upsetting the social order, wrecking marriages, and ruining careers (and commanding respect for precisely those reasons). As such, it was both a narrative blessing and a narrative curse, generating abundant material for plots, but rendering the happy resolution of those plots a fraught and difficult affair. In the tragedies, Shakespeare simply lets the force of romantic love have its natural way with the characters. In the comedies, he employs an array of narrative strategies – including disguises and "bed tricks" –to redirect it toward marriage and resolution. In the problem comedies and romances, those plays that bedevil the traditional genres of tragedy and comedy, Shakespeare actually gives us two endings, a "vile conclusion" that nearly occurs and an actual, comic one that has more the air of a narrow escape from tragedy than a triumphant arrival at comedy.